6x+8=5x-3

Simple and best practice solution for 6x+8=5x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+8=5x-3 equation:


Simplifying
6x + 8 = 5x + -3

Reorder the terms:
8 + 6x = 5x + -3

Reorder the terms:
8 + 6x = -3 + 5x

Solving
8 + 6x = -3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
8 + 6x + -5x = -3 + 5x + -5x

Combine like terms: 6x + -5x = 1x
8 + 1x = -3 + 5x + -5x

Combine like terms: 5x + -5x = 0
8 + 1x = -3 + 0
8 + 1x = -3

Add '-8' to each side of the equation.
8 + -8 + 1x = -3 + -8

Combine like terms: 8 + -8 = 0
0 + 1x = -3 + -8
1x = -3 + -8

Combine like terms: -3 + -8 = -11
1x = -11

Divide each side by '1'.
x = -11

Simplifying
x = -11

See similar equations:

| -4*2-6*2= | | -28=x-2x-7 | | 23/5+87/14= | | 14.4-5=9 | | 10.2-7.3x=-58 | | 13.95-5=9 | | 7y+2(y-5)=5(y+2)-5 | | 3w^2-23w-13=0 | | 5(2q)+(q-4)+q=5 | | 9x+5y+0.1z=100 | | 2(6)(h)+2(h)(17)+2(6)(17)=342 | | 6x=x+6 | | 2(6)(h)+2(h)(17)+2(6)(17)=h | | 12.5y+30+130-30=180 | | 13x-30=100 | | 9r=81 | | (2k+1)(2m+1)= | | -2-ln(x+1)=0 | | 20x^2-2x-4=0 | | 72x^2+96x-936=0 | | 4x+-6=34 | | -2x-(-8+3x)=6 | | y=-3x+-8 | | 3x+12-7*3x=123 | | (y+7)(y-8)= | | 72x^2-2496x-936=0 | | 98-7(10)= | | 98-7(-5)= | | (8x+1)-(-5x+5)= | | 98-7(280)= | | 2x^2-18x+45=0 | | y=5E-06x+0.24 |

Equations solver categories